Comparative genomic analysis and phylogeny of NAC25 gene from cultivated and wild Coffea species - Huded, Arun Kumar C.; Jingade, Pavankumar; Mishra, Manoj Kumar; Ercisli, Sezai; Ilhan, Gulce; Marc, Romina Alina; Vodnar, Dan (Frontiers in Plant Science, 2022)
Coffee is a high value agricultural commodity grown in about 80 countries. Sustainable coffee cultivation is hampered by multiple biotic and abiotic stress conditions predominantly driven by climate change. The NAC proteins are plants specific transcription factors associated with various physiological functions in plants which include cell division, secondary wall formation, formation of shoot apical meristem, leaf senescence, flowering embryo and seed development. Besides, they are also involved in biotic and abiotic stress regulation. Due to their ubiquitous influence, studies on NAC transcription factors have gained momentum in different crop plant species. In the present study, NAC25 like transcription factor was isolated and characterized from two cultivated coffee species, Coffea arabica and Coffea canephora and five Indian wild coffee species for the first time. The full-length NAC25 gene varied from 2456bp in Coffea jenkinsii to 2493bp in C. arabica. In all the seven coffee species, sequencing of the NAC25 gene revealed 3 exons and 2 introns. The NAC25 gene is characterized by a highly conserved 377bp NAM domain (N-terminus) and a highly variable C terminus region. The sequence analysis revealed an average of one SNP per every 40.92bp in the coding region and 37.7bp in the intronic region. Further, the non-synonymous SNPs are 8-11 fold higher compared to synonymous SNPs in the non-coding and coding region of the NAC25 gene respectively. The expression of NAC25 gene was studied in six different tissue types in C. canephora and higher expression levels were observed in leaf and flower tissues. Further, the relative expression of NAC25 in comparison with the GAPDH gene revealed four folds and eight folds increase in expression levels in green fruit and ripen fruit respectively. The evolutionary relationship revealed the independent evolution of the NAC25 gene in coffee.